Elevated baseline plasma IL-8 levels are an independent predictor of long-term all-cause mortality in patients with acute coronary syndrome. Issue 2 (October 2015) - Cavusoglu, Erdal; Marmur, Jonathan D.; Yanamadala, Sunitha; Chopra, Vineet; Hegde, Sudhanva; Nazli, Anila; Singh, Kamal Preet; Zhang, Ming; Eng, Calvin
Abstract: Objectives: To investigate the long-term prognostic significance of baseline plasma IL-8 levels in a group of well-characterized male patients presenting with acute coronary syndrome. Background: IL-8 is a cytokine that has been implicated in the pathogenesis of atherosclerosis and acute coronary syndrome. Elevated plasma levels have been reported in patients with acute coronary syndrome. Methods: Baseline plasma IL-8 levels were measured in 180 male patients with acute coronary syndrome who were referred for coronary angiography and followed prospectively for the development of all-cause mortality for 5 years. Results: In a multivariate model that included a wide variety of baseline clinical, laboratory and angiographic parameters in the selection process, baseline plasma IL-8 levels (analyzed as a continuous variable) emerged as a significant predictor of all-cause mortality at 5 years (HR, 1.43; 95% CI, 1.08–1.88; p = 0.0123). Furthermore, in 3 additional multivariate models that also included in the selection process a number of contemporary biomarkers with established prognostic efficacy in ACS (i.e., NT-proBNP, hs-CRP, hemoglobin and RDW), IL-8 remained an independent predictor of all-cause mortality at 5 years. Conclusion: Elevated baseline plasma levels of IL-8 are associated with an increased risk of long-term all-cause mortality in patients with acute coronary syndrome. Furthermore, this association is independent of a variety of clinical, laboratory and angiographic variables, including contemporary biomarkers with established prognostic efficacy in acute coronary syndrome. Highlights: IL-8 is a cytokine that has been implicated in the pathogenesis of atherosclerosis and ACS. The association of IL-8 with mortality in ACS is independent of clinical, angiographic and laboratory variables. The association of IL-8 with mortality in ACS is independent of other biomarkers with established prognostic efficacy in ACS.